2000
DOI: 10.1111/j.1749-6632.2000.tb06201.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Species in Sickle Cell Disease

Abstract: A BSTRACT : The red cell is a relatively abundant locus of both free radical generation and reaction. Erythrocytes have a high content of unsaturated membrane lipids, a rich oxygen supply and are densely packed with redox-active hemoglobin residues. In response, red cells have a highly evolved and well-integrated network of oxidant defense mechanisms that lend an ability to withstand oxidative stress. In the case of congenital hemoglobin mutations that underlie sickle cell disease, they become very susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 99 publications
(109 reference statements)
2
92
0
1
Order By: Relevance
“…As expected, our experiments detected greater hemoglobin oxidation and lipid peroxidation in the erythrocytes of SS patients. A majority of studies on the SCD population have reported deficits in concentration of GSH (Hebbel et al, 1982;Wetterstroem, 1984;Hebbel, 1990;Hebbel, Leung, Mohandas, 1990;Aslan, Thornley-Brown, Freeman, 2000;Reid et al, 2006;Morris et al, 2008), while others have not found this pattern (Rice-Evans, Omorphos, Baysal, 1986;Somjee et al, 2004;Manfredini et al, 2008;Nur et al, 2011). Moreover, the GSSG (oxidized glutathione)/ GSH index was significantly elevated in SCD patients, supporting an important role for oxidative damage in these cells (Morris et al, 2008;Rusanova, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, our experiments detected greater hemoglobin oxidation and lipid peroxidation in the erythrocytes of SS patients. A majority of studies on the SCD population have reported deficits in concentration of GSH (Hebbel et al, 1982;Wetterstroem, 1984;Hebbel, 1990;Hebbel, Leung, Mohandas, 1990;Aslan, Thornley-Brown, Freeman, 2000;Reid et al, 2006;Morris et al, 2008), while others have not found this pattern (Rice-Evans, Omorphos, Baysal, 1986;Somjee et al, 2004;Manfredini et al, 2008;Nur et al, 2011). Moreover, the GSSG (oxidized glutathione)/ GSH index was significantly elevated in SCD patients, supporting an important role for oxidative damage in these cells (Morris et al, 2008;Rusanova, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In hemoglobinopathies, including sickle cell disease (SCD), red blood cells are rendered more susceptible to oxidative damage because they produce greater amounts of reactive oxygen species (Aslan, Thornley-Brown, Freeman, 2000). Moreover, in SCD red blood cells are more susceptible to oxidation (Chaves, Leonart, Nascimento, 2008) and have a reduced ability to defend against oxidation (Fasola et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, IDA, RBCs produces greater quantities of O 2˙¯, H 2 O 2 and OH˚ than do normal RBC [30]. Besides, iron deficiency anemia, RBCs exhibit increased levels of thiobarbituric acid-reactive substances, suggesting that they are targets for oxidative stress [31]. During deoxygenation of haemoglobin, there is a transfer of electrons between iron atom and O 2 leading to the production of O 2˙¯.…”
Section: Discussionmentioning
confidence: 99%
“…Within the RBC, one of the targets of oxidant damage is the plasma membrane. In the presence of O 2˙¯g enerating system, iron (III) is reduced to iron (II) with subsequent formation of OH˚ and H 2 O 2 [30][31]. The hydroxyl radical oxidizes unsaturated esterified membrane lipids, resulting in changes in fluidity of the bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, F eNO was reduced in SCD patients (11), a possible explanation is reduced nitric oxide (NO) bioavailability resulting from chronic hemolysis and NO scavenging by the cell free hemoglobin (12). A reduced F eNO , however, has not been found in other cohorts (13,14).…”
mentioning
confidence: 99%